Terminal voltage and power regulation using vehicle-to-grid (V2G) schemes integrated to smart interconnected power system - Tarek Hassan Mohamed; Abdel-moamen Mohammed Abdel-Rahim (Institute of Advanced Engineering and Science, 2019)
This paper is an attempt to use the vehicle-to-grid (V2G) connected system to play an effective job in the regulation of the voltage and power of the power system besides its positive effect for the system frequency. A two area power system is used to measure the effectiveness of the proposed V2G scheme. The proposed system is tested under the step load change condition and three phase short system case. A comparison between the system with proposed V2G schemes and that system without V2Gs is carried out showing the importance of the presence of the V2G schemes on system frequency, terminal voltage and total power. MATLAB /SIMULINK software package is used as a test environment.